MORFOGENESIS DAN FISIOLOGIS KETUAAN BUAH JAMBU BANGKOK (PSIDIUM GUAJAVA L.) - SUTARNO, H.; RASYANI, R. (Research Center for Biology-Indonesian Institute of Sciences, 1987)
H. SUTARNO & R. RASYANI. 1987. Morphogeneses and physiological maturity of jambu bangkok (Psidium guajava L.) fruits.Berita Biologi 3(7) : 326 - 329. Studies on nVorphogeneses and physiological maturity of jampu bangkok fruits were carried out from grown i plants in Bogor. Fruits developed from oval to round and nerly egg shape with fruit diameter at about 100 - 110 mm for 18 - 25 weeks. Moisture content and softness of fruits increased slowly at the early time of ripening, but respiration rate increased obviously during period of shape development and ripening. Optimal yield was obtained, when harvesting at the last time of fruit enlargment, i.e. 18 weeks from blooming.